Treatment Effect of Larval Stages by Ecdysone Agonist Hormone (Methoxyfenozide) on The Biology of Cotton Leafworm Spodoptera littoralis (Boisd.) - Ali, H.I.; Ahmed, R.F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
Studies were conducted to evaluate the biological effects of the non-steroidal ecdysone agonist (Methoxyfenozide), on different developmental larval stages of cotton leafworm Spodoptera littoralis (Boisd.) in the laboratory. The results showed that the early larval stages were the most susceptible to Methoxyfenozide which caused 100% mortality within 4-6 days after treatment at all used concentrations, while such percentage of mortality was achieved within 6 days after treatment for late larval stages when the highest concentration was used (0.2)g (ai) /L. Several morphological deformations were noticed on pupal stage, the results showed that the highest percentage of deformations was 12 % and the inhibition of emergence was 63.85% when the concentration 0.08 g (ai) /L was used. Methoxyfenozide negatively affected the fecundity of adults emerged from treated late stages larvae. The results showed that the number of eggs laid per female when treated females and males were paired was 150 eggs/female at 0.08 g (ai) /L concentration, while it was 920 eggs/female in the control. Meanwhile the fertility was reduced to 80% when the treated males and females were mated at 0.08 g (ai) /L.